2019
DOI: 10.1017/pasa.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

The seeds of supermassive black holes and the role of local radiation and metal spreading

Abstract: We present cosmological hydrodynamical simulations including atomic and molecular non-equilibrium chemistry, multi-frequency radiative transfer (0.7-100 eV sampled over 150 frequency bins) and stellar population evolution to investigate the host candidates of the seeds of supermassive black holes coming from direct collapse of gas in primordial haloes (direct-collapse black holes, DCBHs). We consistently address the role played by atomic and molecular cooling, stellar radiation and metal spreading of C, N, O, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 177 publications
(327 reference statements)
3
21
0
Order By: Relevance
“…The effects of alternative choices are small in thin media, but become important in dense sites (e.g. when estimating molecular cooling of collapsing gas or critical fluxes of impinging radiation during the formation of massive black-hole seeds; Luo et al 2020;Maio et al 2019). Neglecting HI shielding corrections at high redshift (z > 5) leads to a large degree of H ionisation and H 2 photodissociation, causing underestimation of HI and H 2 cosmological densities and leading to a trend of the atomic and molecular density parameters in tension with data even at z < 5.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of alternative choices are small in thin media, but become important in dense sites (e.g. when estimating molecular cooling of collapsing gas or critical fluxes of impinging radiation during the formation of massive black-hole seeds; Luo et al 2020;Maio et al 2019). Neglecting HI shielding corrections at high redshift (z > 5) leads to a large degree of H ionisation and H 2 photodissociation, causing underestimation of HI and H 2 cosmological densities and leading to a trend of the atomic and molecular density parameters in tension with data even at z < 5.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although the intensity of the LW background produced by stellar sources and accreting black holes increases very rapidly in the biased region where the bright quasar and its host galaxy are assembling (see Fig. 5 of Valiante et al 2016b), local fluctuations of the LW intensity from nearby sources can significantly exceed the background level, suppressing H 2 cooling and aiding to win the competition between LW radiation and metal winds in heavy seeds hosts (Ahn et al 2009;Regan et al 2014;Dijkstra et al 2014;Inayoshi & Tanaka 2015;Habouzit et al 2016a;Agarwal et al 2017;Maio et al 2019;Mayer & Bonoli 2019).…”
Section: Inhomogeneous Feedbackmentioning
confidence: 99%
“…In fact, in the redshift range where BH seeds are expected to form, the mean LW background is significantly smaller than the required critical value above which H 2 cooling in atomic cooling halos is suppressed, unless the region under investigation is particularly over-dense (Valiante et al 2016a,b). Hence, heavy seeds form when their potential host halo is illuminated by a super-critical J LW from a nearby galaxy (Visbal et al 2014;Habouzit et al 2016b;Regan et al 2019;Maio et al 2019), whose distance must not be too close in order to avoid gas stripping or tidal distortions, which would prevent the formation of the SMS (Chon et al 2016). This motivates the importance of considering the nonlinear spatial distribution of the UV emitting sources around a certain atomic cooling halo, M 1 , candidate to host a heavy or medium-weight seed.…”
Section: Inhomogeneous J Lw Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamical studies of metal-mixing in halos due to external SNe winds have found, however, that the extent of the impact is often over-estimated in large simulations. In practice, metal-pollution in primordial gas is complicated by a number of considerations, including the rate at which winds expel metals from their original galaxies, the propagation of metals through the Intergalactic medium (IGM), and subsequent mixing in gas of varying density (Cen & Riquelme 2008;Maio et al 2019;Smith et al 2015). Recently, Agarwal et al (2017c) devised a semi-analytical model which explores the worst case scenario for DCBH formation, given metal-pollution driven by the same galaxies which provide the necessary LW flux.…”
Section: Narrowing In On the Number Of Dcbhsmentioning
confidence: 99%